The Development and Governance of Private Universities in China - Liu, Xu. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book investigates the form and features of governance and the factors that shape governance in practice in private universities in China. Building on an exploration of the growth of private universities in China after the Communist Party took over the power, the study examines the specific context in China, including the role of the Communist Party, and integrates with shareholders and senior managers to achieve its governance role. It shows that two distinct forms of institutional governance have developed, namely the supervision form and the managerial form. While external policies provide an impetus for change for each university, how key actors in institutional governance understand these policies have significant effect on how the policies are implemented. This can result in change that can be viewed as either symbolic alteration or as operational change. The internal factors that act to shape institutional governance mainly relate to the different developmental stages of the private university, the characteristics of shareholders and senior managers, and the various ways the universities respond to the external policy.
Chapter 1 Introduction -- Chapter 2 Global Development of Private Universities -- Chapter 3 Understanding University Governance in China -- Chapter 4 Theoretical Orientation, Methodology and Research Design -- Chapter 5 Governance in Practice: Three Private Universities -- Chapter 6 Form of Governance and the Factors that Shape It -- Chapter 7 Conclusion.
Keywords: Education and state; Education, Higher; School management and organization; School administration; Educational Policy and Politics; Higher Education; Organization and Leadership